Left Atrial and Left Atrial Appendage 4D Blood Flow Dynamics in Atrial Fibrillation. (September 2016) - Markl, Michael; Lee, Daniel C.; Furiasse, Nicholas; Carr, Maria; Foucar, Charles; Ng, Jason; Carr, James; Goldberger, Jeffrey J.
Abstract : Background—: Atrial 4D flow magnetic resonance imaging was used for the characterization of left atrial (LA) and left atrial appendage (LAA) flow dynamics in patients with atrial fibrillation (AF). Methods and Results—: 4D flow magnetic resonance imaging measured in vivo 3D blood flow velocities in 60 AF patients and 15 controls. Anatomic maps of LA and LAA stasis and velocity were calculated to quantify atrial peak velocity, mean velocity, and stasis (velocities <0.1 m/s). In a substudy with 30 AF patients, 4D flow metrics were compared with Doppler transesophageal echocardiography. For all 15 controls, LAA mean and peak velocities were consistently lower (by 21%/12%; P <0.001) while LAA stasis was higher (by 58%; P <0.001) compared with the LA. In contrast, lower LAA velocity and increased LAA stasis were only found in a fraction (38 of 60) of AF patients. In AF patients, increased CHA2 DS2 -VASc score was associated with significantly ( P <0.043) reduced LA velocities and elevated stasis. There was a heterogeneous expression of atrial flow dynamics, and 25% to 68% of AF patients demonstrated flow in the normal range: 25%/68% for LA/LAA stasis and 38%/60% for LA/LAA peak velocities. Transesophageal echocardiography velocities modestly but significantly ( P <0.05) correlated with 4D flow–based LA velocities ( r =0.41) and stasis ( r =−0.39). Conclusions—: AF resulted in overall impaired but individually variable flow dynamics in both the LA and LAA. AF patients demonstrated atrial flow in the normal range, despite elevated CHA2 DS2 -VASc score.